Numerical analysis of a downsized spark-ignition engine fueled by butanol/gasoline blends at part-load operation. (5th June 2016) - Scala, F.; Galloni, E.; Fontana, G.
Graphical abstract: Highlights: Bio-fuels will reduce the overall CO2 emission. The properties of butanol/gasoline–air mixtures have been determined. A 1-D model of a SI engine has been calibrated and validated. The butanol content reduces the combustion duration. The optimal ignition timing slightly changes. Abstract: In this paper, the performance of a turbocharged SI engine, firing with butanol/gasoline blends, has been investigated by means of numerical simulations of the engine behavior. When engine fueling is switched from gasoline to alcohol/gasoline mixture, engine control parameters must be adapted. The main necessary modifications in the Electronic Control Unit have been highlighted in the paper. Numerical analyses have been carried out at partial load operation and at two different engine speeds (3000 and 4000 rpm). Several n-butanol/gasoline mixtures, differing for the alcohol contents, have been analyzed. Such engine performances as torque and indicated efficiency have been evaluated. Both these characteristics decrease with the alcohol contents within the mixtures. On the contrary, when the engine is fueled by neat n-butanol, torque and efficiency reach values about 2% higher than those obtained with neat gasoline. Furthermore, the optimal spark timing, for alcohol/gasoline mixture operation, must be retarded (up to 13%) in comparison with the correspondent values of the gasoline operation. In general, engine performance and operation undergo little variations when fuel supplying is switched from gasoline to alcohol/gasoline blends.